Prevalence and pattern of abnormalities of cervical smear examination in women attending the fertility clinic at Uniosun Teaching Hospital, Osun state, Nigeria - Ajileye, Ayodeji Blessing; Oseni, Bashiru Shola; Adeniyi, Adesanmi Oladipo (Rzeszów University Press, 2025)
Introduction and aim. Infertility is described as the failure to conceive after one year of unprotected sexual intercourse. One of the causes of female infertility is cervical abnormalities that may be due to bacterial, parasitological, and hormonal imbal ances. The purpose of this study was to determine the prevalence and Pattern of Abnormalities of cervical smear examination in women attending fertility clinic at the University of Osun Teaching Hospital, Osun State, Nigeria. Material and methods. This study was conducted in the fertility clinic of University of Osun Teaching Hospital, Osun State. The study population consisted of 50 infertile (case group) and 50 fertile participants (control group) who are attending the gyne cology clinic of the University of Osun Teaching Hospital, Osogbo. A questionnaire was used to obtain sociodemographic infor mation and other relevant data. Cervical samples were collected using Ayre’s spatula, two smears were made from each subject and stained with Papanicolaou, hematoxylin, and eosin staining techniques. The results were analyzed using a frequency table. Results. Cervical smears revealed atypical squamous cells of undetermined significance in 15 cases (30%), while only 3 (6%) were observed among controls. Cervical cervicitis 19 (38%), Candida spp. (10%), Trichomonas vaginalis (16%), Gardnerella vaginalis (8%), inflammatory cell infiltrate (72%) and increased nucleo-cytoplasmic ratio (26%) were observed between cases and were significantly higher compared with the controls. Conclusion. Abnormal pap smears in this study was significantly more often found in the case group when compared with the controls.
The protocol for this study was sought and approved by the Ethics and research committee of UNIOSUN Teaching Hospital, Osun State, with the approval number UTH/EC/2023/03/746 dated 2 March 2023.
Keywords: infertility; estrogen; Pap smears; progesterone